Development of Skill Assessment Instrument Service Volly 6th Grade in Physical Education - Moh. Noer; Ali Maksum; Anung Priambodo (BIRCU, 2019)
This research aims to develop instruments for assessing lower and upper service engineering skills in volleyball games for 6th-grade students in elementary schools. This research uses research and development methods, with the following development steps: (1) information gathering in the field, (2) analyze the information collected, (3) developing initial products, (4) expert validation and revision, (5) small-scale trials and revisions, (6) large-scale trials and revisions, (7) manufacturing of final products. The subject of this research is 6th-grade students of elementary students. Data analysis for the validity test was carried out with CVR (content validity ratio) and reliability using Alpha Cronbach. This research resulted in a handbook of instrument assessment tools for service techniques of lower and upper service in volleyball games for 6th-grade elementary school students, which contained instructions for use, student assignments sheets, assessment guidelines, assessment rubrics, and scoring tables, which have high validity. (1) And under service reliability initial attitude: r = 0.975, implementation: r = 0.961, follow-up motion: r = 0, 955. Upper Service for initial attitude: r = 0.961, implementation: r = 0.974, follow-up motion: r = 0.989.